Hormones and the resistance of women to paracoccidioidomycosis (2011)
ABSTRACT: Paracoccidioidomycosis, one of the most important endemic and systemic mycoses in Latin America, presents several clinical pictures. Epidemiological studies indicate a striking rarity of disease (but not infection) in females, but only during the reproductive years. This suggested a hormonal interaction between female hormones and the etiologic dimorphic fungus Paracoccidioides brasiliensis. Many fungi have been shown to use hormonal (pheromonal) fungal molecules for intercellular communication, and there are increasing numbers of examples of interactions between mammalian hormones and fungi, including the specific binding of mammalian hormones by fungal proteins, and suggestions of mammalian hormonal modulation of fungal behavior. This suggests an evolutionary conservation of hormonal receptor systems. We recount studies showing the specific hormonal binding of mammalian estrogen to proteins in P. brasiliensis and an action of estrogen to specifically block the transition from the saprophytic form to the invasive form of the fungus in vitro. This block has been demonstrated to occur in vivo in animal studies. These unique observations are consistent with an estrogen-fungus receptor-mediated effect on pathogenesis. The fungal genes responsive to estrogen action are under study.